Cross-resistance phenotypes associated with induction of resistance to isometamidium chloride and quinapyramine sulphate in Trypanosoma congolense - Peregrine, A.S.; Kemei, S.; Ndoutamia, G. (OAU/STRC, 1995)
Isometamidium chloride (Samorin Trypamidium), diminazene aceturate (Berenil, Veriben), homidium chloride (Novidium), homidium bromide (Ethidium) and the salts of quinapyramine (Trypacide, Triquin) are all anti-trypanosomal compounds that are routinely used in domestic livestock. However, the salts of quinapyramine are restricted to use in horses and camels. All four compounds have been used in the field for at least 35 years and the incidence of resistance to each compound appears to be increasing. Furthermore, in some instances, multiple-drug resistance has been Reported and is a particular threat to livestock production. Because isometamidium, homidium, diminazene and quinapyramine are chemically closely related, cross-resistance has been suggested to occur between a number of these compounds and may therefore contribute to the multiple-drug resistance phenotypes observed in the field. However a clear definition of the cross-resistance relationships has not been possible due to the lack of trypanosome populations in which resistance to individual trypanocides has been unequivocally induced. Trypanosoma congolense IL 1180 is a cloned population that expressed a high level of sensitivity to isometamidium chloride, quinapyramine sulphate, homidium chloride and diminazene aceturate; the dose required to cure 50 percent of infected mice (CD 50 value) are 0.018 mg/kg body weight (b.w.), 0.23 mg/kg b.w., 0.37 mg/kg b.w. and 2.3 mg/kg b.w., respectively. In the work described here repeated subcurative treatment of infected Swiss white mice with either isometamidium chloride (Samorin) or quinapyramine sulphate (Trypacide) was used to independently increase the resistance of T. congolense IL 1180 to these two compounds. In the first experiment the resistance of T. congolense IL 1180 to isometamidium was increased to a CD 50 of 1.7 mg/kg b.w. over an 11-month period of drug selection to produce a population designated t. congolense IL 3343. Trypanosoma congolense IL 3341 and T. congolense IL 3342 were intermediate populations produced after 5 and 7 months drug selection, respectively. In order to determine whether Development of resistance to isometamidium resulted in cross-resistance to other anti-trypanosomal compounds, T. congolense IL 3343 was characterised in mice for its sensitivity to diminazene aceturate, homidium chloride and quinapyramine sulphate and had CD 50 values of 7.8 mg/kg b.w., 12.1 mg/kg b.w., respectively. Thus, a 94-fold increase in resistance to isometamidium chloride was associated with a 3-fold increase in resistance to diminazene, a 33-fold increase in resistance to homidium, and a 4-fold increase in resistance to quinapyramine. Values for T. congolense IL 3341 and T. congolense IL 3342 were intermediate between those of T. congolense IL 1180 and T. congolense IL 3343. In a second study, resistance to quinapyramine sulphate was induced in T. congolense IL 1180 over a 7-month period of drug selection, resulting in a population designated T. congolense IL 1180/Stabilate 12. This population had a quinapyramine sulphate CD 50 of > 9.6 mg/kg b.w., and diminazene aceturate, homidium chloride and isometamidium chloride CD 50 values of 12.7 mg/kg b.w., 10.g mg/kg b.w. and 0.10 mg/kg b.w., respectively (Table 2). Thus, an approximately 40-fold increase in resistance to quinapyramine was associated with a 6-fold increase in resistance to isometamidium, 1 28-fold increase in resistance to homidium and a 6-fold increase in resistance to diminazene. In summary, these data indicate that Development of resistance to isometamidium in T. congolense IL 1180 was associated with a high level of cross-resistance to homidium, but low levels of cross-resistance to diminazene and quinapyramine. In contrast, the present data and those from goats indicate that Development of resistance to quinapyramine in the same trypanosome clone was associated with relatively high levels of cross-resistance to isometamidium, homidium and diminazene. These data therefore confirm the rationale for using isometamidium and diminazene as a "sanative" combination, and indicate that the use of quinapyramine in cattle, sheep and goats is contra-indicated since Development of resistance to the compound results in relatively high levels of cross-resistance to all three anti-trypanosomal compounds recommended for use in these livestock species. Finally, since resistance to diminazene is difficult to induce experimentally with diminazene, and such resistance usually occurs in the field as part of a multiple-resistance phenotype (Peregrine, 1994).